The Making of Leaves: How Small RNA Networks Modulate Leaf Development - Yang, Tianxiao; Wang, Yongyan; Teotia, Sachin; Zhang, Zhanhui; Tang, Guiliang (Frontiers in Plant Science, 2018)
Leaf development is a sequential process that involves initiation, determination, transition, expansion and maturation. Many coding genes and a few non-coding small RNAs (sRNAs) have been identified as being involved in leaf development. sRNAs and their interactions not only determine gene expression and regulation, but also play critical roles in leaf development through their coordination with other genetic networks and physiological pathways. In this review, we first introduce the biogenesis pathways of sRNAs, mainly microRNAs (miRNAs) and trans-acting small interfering RNAs (ta-siRNAs), and then describe the function of miRNA-transcription factors in leaf development, focusing on guidance by interactive sRNA regulatory networks.